Hadits Sebagai Sumber Kedalaman Pemikiran Filsafat Islam: Sebuah Analisis Kritis - Hasibuan, Salsabilah; Aqilah, Putri (Yayasan Salam Cerdas Al-Fattah, 2023)
This article aims to outline the role of hadith as a source of depth of thought in Islamic philosophy using critical analysis, explain the relationship between hadith and Islamic philosophy in hadith selection and criticism, explore the challenges and opportunities in integrating hadith with Islamic philosophy. The method used in writing this article is the literature review method with qualitative research on the hadith, i.e. collecting data from the text. The results of the discussion provide the findings that hadith is an important source in philosophy, the biggest challenge in integrating hadith and philosophy is the clash between ratio and revelation, and the opportunity in implementing hadith in life is the phenomenon of Living Hadith.